4D flow magnetic resonance imaging: role in pediatric congenital heart disease. (January 2018) - Lawley, Claire M; Broadhouse, Kathryn M; Callaghan, Fraser M; Winlaw, David S; Figtree, Gemma A; Grieve, Stuart M
Imaging-based evaluation of cardiac structure and function remains paramount in the diagnosis and monitoring of congenital heart disease in childhood. Accurate measurements of intra- and extracardiac hemodynamics are required to inform decision making, allowing planned timing of interventions prior to deterioration of cardiac function. Four-dimensional flow magnetic resonance imaging is a nonionizing noninvasive technology that allows accurate and reproducible delineation of blood flow at any anatomical location within the imaging volume of interest, and also permits derivation of physiological parameters such as kinetic energy and wall shear stress. Four-dimensional flow is the focus of a great deal of attention in adult medicine, however, the translation of this imaging technique into the pediatric population has been limited to date. A more broad-scaled application of 4-dimensional flow in pediatric congenital heart disease stands to increase our fundamental understanding of the cause and significance of abnormal blood flow patterns, may improve risk stratification, and inform the design and use of surgical and percutaneous correction techniques. This paper seeks to outline the application of 4-dimensional flow in the assessment and management of the pediatric population affected by congenital heart disease.